PENDEKATAN “RELIGIOUS MARKETING” DALAM KOMUNIKASI ISLAM MENJAWAB TANTANGAN ERA DISRUPSI - Muhammad Mabrur (Alhadharah: Jurnal Ilmu Dakwah, 2020)
The rapid development of information technology has influenced the behavior of modern human life. Findings after findings have made modern humans connected with each other. Impact The emergence of new business features that shift the old life patterns. This is where disruption begins. Disruption is a change in various sectors of life as a result of digitalization and the "Internet of Thing" ("IoT)". . However, he can shift the pattern of old life. The collapse of a giant brand such as the Blackberry, Kodak, Nokia, has become a strong warning that gives 2 choices: adapt or die. Islamic communication / Islamic propaganda was not immune from the influence of disruption. When he is not managed neatly it is not impossible he will sink with his teachings. Especially when he is in the middle of millennial generation who has a unique character full of freedom. One alternative approach that can be offered is the Religious Marketing approach. Commercial marketing has succeeded in changing patterns of consumer behavior. The same expectations when the concept of marketing are applied in the process of Islamic communication. The study of Islamic Communication using the Religious marketing approach is based on a logical planning process that involves consumer-oriented research, marketing analysis, marketing segmentation, determining branding goals and identifying marketing strategies and tactics. Various other knowledge are also involved in studies such as the theories of psychology, sociology, anthropology and communication in order to understand how to influence people's behavior.